Two new combinations in Elatostematoides (Urticaceae) for species from Sarawak and Sumatra - Rodda, Michele; Tseng, Yu-Hsin; Monro, Alexandre K. (Phytotaxa, 2020)
Based on a recently published phylogeny, Elatostematoides is monophyletic and distinct from Elatostema. As more taxa are included in the molecular phylogeny, new combinations will need to be created to accommodate in Elatostematoides species formerly in Elatostema. In the present paper we provide evidence that Elatostema hirtum belongs to Elatostematoides. New combinations in Elatostematoides for Elatostema hirtum and the similar Elatostema scandens are proposed, resulting in the first additions to the genus since 1934.